Eighteenth‐century queer studies, revisited. Issue 7 (20th August 2021) - Chow, Jeremy
Abstract: This review essays opens with concerns over "crisis" that have spurred widespread panic about the state and future of the humanities. Crisis, I suggest, is the rallying call for new directions in and reinvention of 18th‐century queer studies. By advocating for recuperative histories wherein crisis is a motivational force that pushes 18th‐century queer studies to be further self‐reflexive and intersectional, I examine three potent trends and their portents for 18th‐century studies: masculinity studies, the nexus of queer and disability studies, and trans studies. I close with a continued call for examinations of queerness and race as they might enlighten the long 18th century. This article ultimately surveys current terrains of 18th‐century queer studies and its commitments to evolve inclusively, dynamically, and unapologetically.